Design, synthesis, molecular docking and molecular dynamics studies of some 3-methoxy flavone derivatives as an anti-breast cancer agent - Bharti S. Fegade; Somadatta Y. Chaudhari; Rupali V. Likhar; Ritesh P. Bhole; Pravin S. Uttekar; Sandeep S. Pathare; Swastika Maitra; Daniel Ejim Uti; Magdi E. A. Zaki; Esther Ugo Alum (Discover Oncology)
Abstract Objective The present study aimed to synthesize flavone hybrids with 3-methoxy substitution and an N-heterocyclic ring at the 4ʹ position of the flavone B ring and test their effectiveness against cancer. Method Molecular docking of 3-methoxy flavone was studied on ER-α and EGFR. By cyclizing chalcones, various flavonol derivatives were synthesized and 3-methoxy flavones were produced by flavonol methylation. 3-methoxy flavone derivatives substituted with various heterocyclic rings like morpholine, piperidine, N-methyl piperazine, pyrrolidine, triazole, imidazole, and benzimidazole were synthesized. 1HNMR, 13CNMR, IR, and mass spectra verified all compound’s structures. 3-methoxy flavone derivatives evaluated for their anticancer potential by MTT assay and SRB assay on breast cancer (MCF-7 and MDA-MB-231). The molecular dynamics simulation was also studied for active compounds on the human estrogen receptor alpha and epidermal growth factor receptor. Results 3-methoxy flavone derivatives were successfully synthesized and evaluated by spectroscopic studies. The MTT assay on MCF-7 cell lines revealed significant cytotoxic activity of compounds Ciii and Civ by expressing IC50 values of 13.08 ± 1.80 and 20.3 ± 1.47 µg/ml, respectively. The SRB assay on MDA-MB-231 showed a potent response by compounds Cii, Cv & Cvi with IC50 values of 5.54 ± 1.57, 5.44 ± 1.66 and 8.06 ± 1.83 µg/ml, respectively. Overall results showed the effective substitution of 3-methoxy flavone was N-methyl piperazine and piperidine in all cell lines, while triazole substitution was effective in MDA-MB-231 cells. Molecular dynamics study proved the stability of synthesized compounds’ ligands-protein complexes. The structure–activity relationship of flavone derivatives suggests the electron donating group increases the anticancer activity of derivatives in MDA-MB-231, while the same is not reflected in MCF-7 cell lines. Conclusion This study provides a foundation for designing flavone derivatives with N-heterocyclic ring incorporation as anticancer medicines.